EFFICACY OF A SINGLE-INJECTION SODIUM HYALURONATE TREATMENT IN LATERAL EPICONDYLITIS - Khan, Inam Ullah; Awan, Abdus Saboor; Khan, Aimal Sattar; Marwat, Imran; Meraj, Muhammad (Journal of Ayub Medical College Abbottabad, 2018)
Background: Lateral epicondylitis or tennis elbow is a disease of tendons arising from common extensor origin at the lateral epicondyle of elbow and is commonly characterized by pain on supination of forearms as well as extension of fingers and wrists. Methods: This descriptive case series aims to determine the efficacy of a single-injection sodium hyaluronate treatment for lateral epicondylitis. The study was conducted at the Department of Orthopaedics. Ayub Teaching Hospital Abbottabad. From February 1 to August 31, 2014. Patients diagnosed with lateral epicondylitis were administered 1 cc of 1% Sodium hyaluronate 1 cm from the lateral epicondyle into the soft tissue. Results: Hyaluronic acid is more effective in patients with moderate pain of lateral epicondylitis (VAS score ‰¤7 than in patients with severe pain (VAS score >7). Paired sample t-test was used to compared the means of the pre- and post-procedure VAS score and the difference was found to be statistically very significant (p=0.00) with a mean±SD change in VAS of 2.31±1.35 at 4 weeks. Conclusion: A single injection of sodium hyaluronate is effective in management of moderate, but not severe pain of lateral epicondylitis. Keywords: Elbow; lateral epicondylitis; pain; sodium hyaluronate; tennis; corticosteroids